The bacteriophage LUZ24 “Igy” peptide inhibits the Pseudomonas DNA gyrase - Jeroen De Smet; Jeroen Wagemans; Maarten Boon; Pieter-Jan Ceyssens; Marleen Voet; Jean-Paul Noben; Julia Andreeva; Dmitry Ghilarov; Konstantin Severinov; Rob Lavigne (Cell Reports, 2021)
Summary: The bacterial DNA gyrase complex (GyrA/GyrB) plays a crucial role during DNA replication and serves as a target for multiple antibiotics, including the fluoroquinolones. Despite it being a valuable antibiotics target, resistance emergence by pathogens including Pseudomonas aeruginosa are proving problematic. Here, we describe Igy, a peptide inhibitor of gyrase, encoded by Pseudomonas bacteriophage LUZ24 and other members of the Bruynoghevirus genus. Igy (5.6 kDa) inhibits in vitro gyrase activity and interacts with the P. aeruginosa GyrB subunit, possibly by DNA mimicry, as indicated by a de novo model of the peptide and mutagenesis. In vivo, overproduction of Igy blocks DNA replication and leads to cell death also in fluoroquinolone-resistant bacterial isolates. These data highlight the potential of discovering phage-inspired leads for antibiotics development, supported by co-evolution, as Igy may serve as a scaffold for small molecule mimicry to target the DNA gyrase complex, without cross-resistance to existing molecules.